Promosi Melalui Media Sosial Facebook dan Twitter dan Pengaruhnya terhadap Kunjungan Wisatawan di Jungleland Adventure Theme Park - Moch. Dicky Dewatara (Journal of Tourism Destination and Attraction, 2014)
The potential of social media as a tool to attract visitors are now widely used by many tourist destinations, including by Jungleland Adventure Theme Park. Facebook and Twitter are two social media used by Jungleland Adventure Theme Park as campaign media to attract visitors because these two highly interactive social media has been popularly used by people around the world. This research aims to determine the role and influence of the social media promotion toward visitor in Jungleland Adventure Theme Park. The method used is a quantitative method. The results showed that the promotion through social media Facebook and Twitter affect the travelers traffic to visit Jungleland Adventure Theme Park. Because both social media is informative and delivered information regularly, so travelers who want to get the info directly visit to Jungleland Adventure Theme Park.